Analisa Menguatnya Politik Identitas pada Pemilihan Kepala Daerah Kabupaten Lampung Timur dan Kabupaten Pringsewu - Indrajat, Himawan; Warganegara, Arizka; Muflihah, Lilih (Wacana Publik, 2024)
Direct regional elections are a form of implementing democracy at the local level, after previously regional elections were held indirectly elected through the Rakyar Regional Representative Council constituencies with this method were still carried out at the beginning of the 1999 reform regulated through Law Number 22 of 1999 concerning Regional Government, but then with the spirit of democratization regional elections were finally held directly where the people were the ones who determine who is eligible to be the regional head and its implementation was first carried out in 2005 based on Law Number 32 of 2004 concerning Regional Government. But in its implementation, it turns out that dynamics emerge, especially efforts made by candidates for regional heads to win contestations using tribal and religious sentiments or known as Identity Politics. The use of identity politics in local elections also occurred in the regional elections of East Lampung and Pringsewu districts to win regional elections in these areas.